Behavioural Insights for Strategic Planning - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).03, 2025)
This paper explores the integration of behavioural economics into strategic planning frameworks to enhance decision-making in uncertain and complex environments. By unpacking foundational concepts such as cognitive biases, heuristics, and bounded rationality, the discussion challenges traditional assumptions of rational economic behaviour. Practical tools such as nudging, framing, and choice architecture are evaluated for their efficacy in influencing consumer and employee behaviour. The study further distinguishes between risk and uncertainty, proposing adaptive strategies like scenario planning and real options analysis to improve organisational resilience. Drawing on behavioural game theory, the paper offers insights into market competition, highlighting real-world case studies across industries. These show the practical utility of behavioural approaches in achieving sustainable competitive advantage and strategic goals .